Czynniki społeczne w genezie nieprawidłowego rozwoju i zachowania - Siwek, Stanisław (Acta Universitatis Lodziensis. Folia Psychologica, 2010)
The paper deals with the impact of the social background for developmental disorders, searching for unfavorable factors in the three most important surroundings – family, school, contemporary group. Hence the analysis was made with signs of improper interpersonal relations and life conditions encroaching on mental balance that can be found in social agencies (school, family), responsible for personal development and behavior. Basing upon selected theoretical works and my diagnostic and therapeutic experience, various negative effects on personal development were illustrated, given the ill-adapted familial and educational systems, as well as informal roles played in contemporary groups. The paper got its material focused on the familial environment where personality traits and parental attitudes, ways of communication and pathological mechanisms permanently generate factors that appear unfavorable for personal social development (toxic messages, enforced loyalty, role delegation,collusion relationships). A particular emphasis was put on the role of social factors in the origins of both primary and secondary disorders, and on the fact that signs of difficulties and disorders a youngster meets may be an indirect reaction to factors infringing on his/her psychological balance or else – actualized belatedly when assuming new social roles.